SUSTAINABLE LIVING GENERASI MILENIAL DALAM MENANGGULANGI SAMPAH: Sustainable Living Milenial Generation in Treating Waste - Dewi, Ni Made Nia Bunga Surya (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The amount of plastic waste continues to increase every day along with the increasing number of products and consumption patterns of the millennial generation. The only way to overcome this increasing volume of plastic waste is to reduce the amount of plastic waste from its source by encouraging millennials to care about the use of goods and services. The problem in this study is to explain how the role of sustainable living of the millennial generation in plastic waste management and how the current level of sustainable living of the millennial generation. This research uses a descriptive method to describe how millennials' sustainable living in reducing plastic waste. The results show that as a form of millennial generation participation in efforts to improve the environment, millennials have implemented sustainable living in their daily lives such as using tumblers, bringing their own shopping bags, sorting waste starting from their own home environment. The current millennial generation contributes to the practice of sustainable living doing these activities without being forced. They fall into the moderate category where they play a role in plastic waste management but still do not do it fully